Phylogeographic structure and historical demography of tarakihi ( Nemadactylus macropterus ) and king tarakihi ( Nemadactylus n.sp.) in New Zealand - Yvan Papa; Alexander G. Halliwell; Mark A. Morrison; Maren Wellenreuther; Peter A. Ritchie (New Zealand Journal of Marine and Freshwater Research, 2022)
Tarakihi ( Nemadactylus macropterus ) is a demersal fish that supports valuable commercial, recreational, and customary fisheries in New Zealand. However, little is known about its stock structure. The population genetic structure, genetic diversity, and demographic history of N. macropterus were investigated using the hypervariable region one of the mitochondrial control region. 370 samples from 14 locations around New Zealand were collected. While weak genetic breaks were detected between Hawke's Bay and East Northland and between the west and east coasts of South Island, no clear genetic structure was detected for the overall New Zealand area (Ф ST = 0.002, P = 0.18), indicative of a panmictic genetic structure. N. macropterus display a high level of genetic diversity and appear to have a historically large and stable population with a long evolutionary history. Bayesian skyline analysis indicates that the historic population has gone through two expansions, likely caused by repeated glacial cycles during the second half of the Pleistocene. The addition of 15 king tarakihi samples ( Nemadactylus n.sp.) collected from the Three Kings Islands showed a clear genetic differentiation between the two morphotypes. These findings can inform the future management of N. macropterus and N . n.sp. to ensure a sustainable harvest.